Does cultural and linguistic diversity affect health-related outcomes for people with stroke at discharge from hospital? - Davies, S.; Dodd, K.; Hill, Keith (Informa Healthcare, 2017)
Purpose: Primary purpose to determine if cultural and linguistic diversity affects health-related outcomes in people with stroke at discharge from hospital and secondary purpose to explore whether interpreter use alters these outcomes. Method: Systematic search of: Cochrane, PEDro, CINAHL, Medline, Pubmed, Embase, PsycINFO and Ageline databases. Publications were classified into whether they examined the impact of diversity in culture, or language or culture and language combined. Quality of evidence available was summarized using Best Evidence Synthesis. Results: Eleven studies met inclusion criteria and were reviewed. Best Evidence Synthesis indicated conflicting evidence about the impact of culture alone and language barriers alone on health-related outcomes. There was strong evidence that hospital length of stay does not differ between groups when the combined impact of culture and language was investigated. Conflicting evidence was found for other outcomes including admission, discharge and change in FIM scores, and post-hospital discharge living arrangements. It is unknown if interpreter use alters health-related outcomes, because this was infrequently reported. Conclusion: The current limited research suggests that cultural and linguistic diversity does not appear to impact on health-related outcomes at discharge from hospital for people who have had a stroke, however further research is needed to address identified gaps.Implications for RehabilitationThe different language, culture and beliefs about health demonstrated by patients with stroke from minority groups in North America do not appear to significantly impact on their health-related outcomes during their admission to hospital.It is not known whether interpreter use influences outcomes in stroke rehabilitation because there is insufficient high quality research in this area.Clinicians in countries with different health systems and different cultural and linguistic groups within their communities need to view the results with caution as further investigation is required outside North America to ensure optimal and equitable care for these groups.In the absence of clear outcomes from high quality research, clinicians should ensure patients and their families have an optimal understanding of the health condition, the rehabilitation process and the service system, irrespective of language or cultural differences.